(untitled) (Scientific journal of the Fergana State University, 2026)
The article considers the creative potential of teachers undergoing professional development as the main issue, the development of their professional and personal qualities, the causes and solutions to the problems encountered during their work. The intended purpose is to analyze the factors that hinder their personal development in adult education and work, and to study the reasons that motivate them. Practical situations show that, in addition to their personal and character traits, external environmental factors also hinder the manifestation of creativity in adults. For these reasons, in developing the personal and creative potential of teachers undergoing professional development, the following methods are recommended: “Divergent thinking tests”, “TORRANCE creative thinking tests”, “Expert assessment”, which help to further develop their professional skills in the art of establishing communication with others, initiative in establishing value relations in various fields, social activity in knowledge and work, and continuous professional development. According to the results of the empirical research, specialists have become familiar with the methods of eliminating objective and subjective reasons that depend on them. As a result, their professional activities and attitudes towards social life have developed in a positive direction. In conclusion, we can say that personal and creative potential acts as a motivating force that encourages the development of the individual in social life and during professional activities.